Energetic Evaluation of the Feeding-in of Hydrogen into the Natural Gas Distribution System - Müller, Karsten; Geng, Jin; Völkl, Johannes; Arlt, Wolfgang (Chemie Ingenieur Technik, 2012)
The proceeding increase in the share of renewable energies requires a fast allocation of chemical energy storage capacities. One option is the feeding-in of renewable hydrogen into the natural gas distribution system. A thermodynamic evaluation shows that the feeding-in has a good overall efficiency compared to other chemical storage technologies. Due to the limited intake capacity of the distribution system, the available capacities are not sufficient for a total shift of the energy system to renewable sources. Nevertheless, it can, as one of a group of measures, contribute to a general energy storage system.
Keywords: Chemische Speicher; Energiespeicher; Erdgasnetz; Exergie; Wasserstoffeinspeisung; Chemical storage; Energy storage; Exergy; Feeding-in of hydrogen; Natural gas distribution system